2012
DOI: 10.1186/1471-2393-12-74
|View full text |Cite
|
Sign up to set email alerts
|

Institutional delivery service utilization and associated factors among mothers who gave birth in the last 12 months in Sekela District, North West of Ethiopia: A community - based cross sectional study

Abstract: BackgroundReduction of maternal mortality is a global priority particularly in developing countries including Ethiopia where maternal mortality ratio is one of the highest in the world. The key to reducing maternal mortality ratio and improving maternal health is increasing attendance by skilled health personnel throughout pregnancy and delivery. However, delivery service is significantly lower in Amhara Regional State, Ethiopia. Therefore, this study aimed to assess factors affecting institutional delivery se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
181
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(274 citation statements)
references
References 5 publications
(8 reference statements)
77
181
14
2
Order By: Relevance
“…Mothers who travel less than one hour by bare foot to reach to the nearby health institute were 5 times more likely to give birth in the health institution than mothers who travel more than 2 h and those who travel 1-2 times were 7 times more likely to delivery in the health institution than those mothers who travel more than 2 h. This study also revealed that mothers who visited ANC during last pregnancy were about 2 times more likely to deliver in health facilities than mothers who did not visit ANC which was Similar to studies conducted in north Gondar, Sekela district and in Metekel Zone [6][7][8].…”
Section: Citationsupporting
confidence: 79%
See 1 more Smart Citation
“…Mothers who travel less than one hour by bare foot to reach to the nearby health institute were 5 times more likely to give birth in the health institution than mothers who travel more than 2 h and those who travel 1-2 times were 7 times more likely to delivery in the health institution than those mothers who travel more than 2 h. This study also revealed that mothers who visited ANC during last pregnancy were about 2 times more likely to deliver in health facilities than mothers who did not visit ANC which was Similar to studies conducted in north Gondar, Sekela district and in Metekel Zone [6][7][8].…”
Section: Citationsupporting
confidence: 79%
“…This study finding was higher than National EDHS result of 2011 and the study done in Sekela District in 2012 which was 10% and 12.3% respectively; this might be due to the time gap, i.e., since 2011 there could be improvement in accessing and utilizing the service and probably due to relatively good commitment of the district health office and health professionals working there [5,6].…”
Section: Discussioncontrasting
confidence: 47%
“…Previous local studies done in Ethiopia showed that there were variation in skilled birth attendance, 12.3% in Munisa district [6], 4.3% of rural mothers and 40% urban mother in Arsi [7], 12.0% (20.8% in urban and 6.8 % in rural mother) in Metekel [8], 13.5% in North Gondar [9], 12.1% in Sekela district [10]. Previous studies also showed that institutional delivery service utilization were associated with educational status of mothers and their husbands, income level, preferences of the attentions of their relatives, trust on traditional birth attendants, absence of health problems during pregnancy, antenatal visits during pregnancy, short duration of labor, mothers' place of residence, age, perceived distance to the nearest health facility and transportation costs [6,7,8,9,10]. However, little is known about institutional delivery service utilization in Woldia, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that 68.2% of the participants had more than one hour of distance to birthing facility, whereas in a study conducted by Shah R only 24% of women had one hour or more distance to birthing facility 13 . Another study conducted by Teferra A.S. showed that 19.4% had one to two hours of time taken to visit the nearby health center 17 .…”
Section: Resultsmentioning
confidence: 99%